Public support for R&D, knowledge sourcing and firm innovation: Examining a mediated model with evidence from the manufacturing industries - Lucena Pimentel, Abel Ernesto; Afcha Chávez, Sergio Moisés (CENTRUM Publishing, 2014)
The aim of this study is to examine how firms realize the benefits associated with public support for R&D programs. To do so, this research proposes and tests the hypothesis that the level of knowledge sourcing applied by a firm during the innovation process mediates the relationship between granted R&D subsidies and a firm’s innovative performance. Using a panel of Spanish manufacturing companies, the findings provide evidence to indicate that the degree of firms’ investments in intramural R&D and the levels of openness in their innovation serve as mediating mechanisms between R&D subsidies and firm innovation, as measured by patent application and new product introduction counts. The study advances the literature on innovation management and technology-policy evaluation by showing how firms use their knowledge-sourcing strategies to exploit opportunities provided by public intervention.
Keywords: Intramural R&D; Open innovation; Firm innovative performance; Innovation policy; Mediation analysis; http://purl.org/pe-repo/ocde/ford#5.02.04